Sistem Informasi Penggajian Kantor Pertanahan Provinsi Papua Tengah Kabupaten Nabire - Gunawan Prayitno; Sulastri Arung Sombolinggi; Kristia Yuliawan (STMIK Pesat Nabire, 2024)
The payroll system is one of the topics related to managing employee welfare, so companies/offices must pay attention to it in order to achieve their goals. With an adequate payroll system, payroll can be made systematically to pay wages according to each employee's rights from the start, and errors in payroll are undesirable. Problems that occur in the Nabire Land Office payroll system currently include data that has not been stored properly because it has not used a payroll information system, employee salary data must be checked repeatedly in the columns filled in using Excel tools, errors occur in calculating employee salaries and processing slips. salary that counts for a long time. Apart from that, in making salary receipts every month, you have to manually record data on permanent Rapid Application Development(RAD). This helps the Nabire Papua Land Office to develop a better and more efficient payroll system by addressing the problems mentioned above. The system should be designed to be easy to use, allowing for easy customization and customization of the system.